Isolation and polymerase chain reaction confirmation of Brucella melitensis from goats in Malaysia. - Bamaiyi , Pwaveno Huladeino; Hassan, Latiffah; Bejo, Siti Khairani; Mohamed, Zainal Abidin; Mahmod, Ramlan; Krishnan, N.; Adzhar, A.; Abdullah, N.; N.H.M, Hamidah; M.M, Norsuhanna; Hashim, S.N. (2011)
A study was carried out to isolate Brucella melitensis using established bacteriological techniques and the Polymerase Chain Reaction in previously known positive goat farms in Selangor, Negeri Sembilan, Melaka and Pulau Pinang states of Malaysia. A total of 7 isolates were recovered from vaginal swabs, spleen and uterine fluid using standard biochemical tests with vaginal swabs yielding the highest isolates of 4 (57.14%) followed by the spleen 2 (28.57%) and uterine fluid 1(14.29%). No isolates were recovered from the lymph nodes. PCR confirmed all 7 isolates as B. melitensis